Contrary response of porcine articular cartilage below and over 1000 s−1. (December 2021) - Tran, D.T.; Juang, Y.C.; Tsai, L.
Abstract: Background: Knee joints experience excessive loads quite frequently during sports activities, and these shocks could accelerate progressive degeneration in articular cartilage. Methods: Quasi-static and dynamic response of porcine knee articular cartilages were investigated in this research. Split Hopkinson Pressure Bars (SHPB) were utilized to examine the articular cartilage properties at strain rates between 0.01–2000 s −1 . Findings: The results showed that strain rate is an important factor for articular cartilages, distinctively divided into above and below 1000 s −1 . The articular cartilages exhibit a strain hardening phenomenon when shock loaded at strain rates under 1000 s −1 . When loaded at strain rates over 1000 s −1, their ultimate strength and elastic modulus decreased with increasing strain rates. Interpretation: The biphasic structure of the cartilage explained the change of modulus. At the lower strain rates, fibers realigned and solidified the structure, while at higher strain rates, there is not enough time for the tissue fluid to move inside the cartilage, leading to a reduction in the deformability of the specimen and raising of Young's modulus. The results can be utilized to provide some useful data for biomaterial and computational works in the future. Highlights: Influence of strain rates from 0.01 to 2000 s −1 on porcine articular cartilage studied Hopkinson bar was utilized to provide steady strain rates between 500 and 2000 s −1 Stress-strain curves indicate contrary strain rate dependence below and over 1000 s −1 Thickness has no effect on the stiffness of the articular cartilage